A Study of Symbolism in Josh Malerman's Bird Box - Rehan Syach Jihan; Adeline Grace M. Litaay (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This article is about A Study of Symbolism in Josh Malerman’s Bird Box. The plot is a post-apocalyptic thriller that follows Malorie, a young woman navigating a world invaded by unknown creatures who, when seen, drive people insane and to suicide. This article exposed the symbols and their meaning in Josh Malerman’s Bird Box. The approach used in this study is an intrinsic approach because symbol is one element of intrinsic approach. Frederick William Dillistone’s symbolism theory is used to analyze symbols and their meaning. Descriptive qualitative research methods are used in this study. Qualitative research uses non-numerical data to comprehend people's beliefs, experiences, attitudes, behavior, and interactions. The results of this study show that there are 9 symbols used in the story: 1. Birds which symbolize alarm, 2. Blindfold which symbolize protection, 3. Motherhood which symbolize sacrifice, 4. River which symbolize journey, 5. Unseen Entity which symbolize fear and terror, 6. Safe House which symbolize safety and security, 7. Draw Well which symbolize medicine, 8. Dogs which symbolize guide, 9. Box which symbolize physical barrier and hope. The results of this thesis demonstrate the intricacy and potency of symbolism in Bird Box. The symbols explored in the study deepen the readers' understanding of the novel's themes, heighten the narrative's emotional impact, and contribute to the broader conversation on the power of symbolism in contemporary literature.